Epidemiology and burden of bipolar disorder in Africa: a systematic review of data from Africa (2016)
Background Bipolar disorder impacts negatively on the patient, the family, as well as the society. It taxes the health care services due to a combination of the illness with associated medical and psychiatric comorbidities. In Africa, unfortunately, knowledge of the epidemiology and burden of bipolar disorder is based mainly on studies from the USA and Europe. In this systematic review of literature from Africa, we highlight the epidemiology and burden of bipolar disorder. Methods A systematic review of publications from Africa relating to the epidemiology and burden of bipolar disorder was conducted. Result Data from community surveys conducted in Nigeria and Ethiopia indicated a lifetime prevalence estimate of 0.1 % to 1.83 for bipolar disorder. Missed diagnosis rate of bipolar disorder was up to 36.2 %. In one study, 8.1 % of the males and 5.4 % of the females reported a previous suicide attempt. A study showed that up to 60 % of patients with bipolar disorder had at least one comorbidity. There were no reports on all-cause mortality and cost of illness. Conclusion Bipolar disorder is a major mental health problem in Africa. Scientific findings on bipolar disorder from Africa are consistent with the existing literature from other parts of the world. There still exists a dearth of high-quality studies addressing the epidemiological, clinical, social, and economic burden of the disorder.